Karst topography: Formation, processes, characteristics, landforms, degradation and restoration: A systematic review - Belay Zerga (Watershed Ecology and the Environment)
Karst refers to any topography or landform that forms over soluble rocks. The classic karst landforms, which include enclosed depressions, sinking streams, and caves, are primarily generated by surface and subsurface waters dissolving rocks; mechanical erosion plays a secondary role. This review paper attempted to evaluate the Karst topography from an international standpoint, taking into account its creation, features, resultant landforms, denudation, and restoration. The systematic review of the literature, which has been shown to be a trustworthy approach, served as the foundation for this review article. The review shower that iypically, karst topography forms on evaporites, dolostones, limestones, and rock salt. Caves can contain significant paleontological, paleoenvironmental, and archeological remnants because they can serve as traps for surface material, shielding it from surface erosion. Karst cannot be produced solely by a significant amount of rock solubility. The best karst is developed by dense, massive, pure, and coarsely fractured rocks. Although karst terrain is most common in humid areas with carbonate rock, it can also be found in temperate, tropical, alpine, and polar climates. According to the Köppen-Geiger classification, arid climates account for approximately 34.2% of all carbonate rock areas worldwide. Cold climates account for 28.2%, moderate temperatures for 15.9%, tropical climates for 13.1%, and polar climates for 8.6% of the total. Ten percent of the Earth’s surface is made up of karst topography, and up to 25% of the world’s population depends on karst areas for their water supply, making an understanding of karst essential. The peculiarities of karst environments make them highly vulnerable to geohazards such as collapse and dropout dolines (sinkholes), slope movements, and floods. Karst areas are also extremely specialized habitats, with important and often very vulnerable subterranean ecosystems. The vulnerability of karst requires unique management and protection strategies to be devised to preserve this natural landscape for its future sustainability.